Molecular design of light-harvesting photosensitizers: effect of varied linker conjugation on interfacial electron transfer. Issue 28 (1st July 2016) - Jiang, Jianbing; Swierk, John R.; Hedström, Svante; Matula, Adam J.; Crabtree, Robert H.; Batista, Victor S.; Schmuttenmaer, Charles A.; Brudvig, Gary W.
Abstract : Interfacial electron transfer dynamics of a series of photosensitizers bound to TiO2 via linkers of varying conjugation strength are explored by spectroscopic and computational techniques. Abstract : Interfacial electron transfer dynamics of a series of photosensitizers bound to TiO2 via linkers of varying conjugation strength are explored by spectroscopic and computational techniques. Injection and recombination depend on the extent of conjugation in the linker, where the LUMO delocalization determines the injection dynamics but both the HOMO and HOMO−1 are involved in recombination.